Analysis for effects of ultrasonic power on ultrasonic vibration-assisted single-pulse laser drilling. (November 2018) - Xia, Kaibo; Ren, Naifei; Wang, Houxiao; Shi, Chunhui
Highlights: Ultrasonic-assisted single-pulse laser drilling is reported. Report influence of ultrasonic power on single-pulse laser drilling quality. Higher ultrasonic power improves hole geometry with more uniform recast layer. Abstract: An investigation of water-based ultrasonic-assisted single-pulse laser drilling is reported for drilling thin section super-alloy sheets to show the influence of ultrasonic power on both blind-hole drilling quality and through-hole drilling quality using different single laser pulses. The effects of ultrasonic power on drilling quality (e.g., hole geometry, hole sidewall surface morphology, and hole wall recast layer, etc.) were experimentally investigated for ultrasonic-assisted millisecond single-pulse Nd:YAG laser drilling. It was found that the ultrasonic vibration incorporated into the single-pulse Nd:YAG laser drilling process could obviously improve the inner hole wall surface morphology/quality in terms of relatively clean and better-profiled hole wall surface with less defects/spattering, better uniformity, and smaller surface roughness. It was indicated that the alteration of the molten material flowing/spattering/expelling due to the contribution of ultrasonic vibration was the main reason of improving the drilling quality for ultrasonic vibration-assisted single-pulse laser drilling. It was also shown that the influencing trends of ultrasonic power on hole circularity deviation, hole sidewall surface morphology, and hole sidewall surface roughness for through holes were similar to those for corresponding blind holes. Except the sample sheet thickness difference, under the same other drilling conditions, hole cross sections and recast layers contributed to the main differences between the drilled through holes and blind holes, which was mainly caused by their difference of the flow and expelling of the molten material.